2010
DOI: 10.5301/jbm.2010.6088
|View full text |Cite
|
Sign up to set email alerts
|

Use of Serum Circulating Ccnb2 in Cancer Surveillance

Abstract: Cyclin B2 (CCNB2), a member of the cyclin protein family, has been found to be up-regulated in human cancers. To evaluate the potential use of circulating CCNB2 in serum in cancer surveillance, we examined relative expression levels of serum circulating CCNB2 mRNA in 103 cancer patients, 19 normal controls, and 40 benign disease patients using real-time quantitative reverse transcriptase polymerase chain reaction. We found that the relative expression level of circulating CCNB2 mRNA in cancer patients was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
0
28
0
1
Order By: Relevance
“…In addition, the transcripts here identified not only may predict prognosis (relative quantification values were significantly associated with poor survival), but may also be selected as future targets for therapy (gene therapy or chemotherapy), as previously reported in various human cancers [37], [47], [53], [64], [72].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In addition, the transcripts here identified not only may predict prognosis (relative quantification values were significantly associated with poor survival), but may also be selected as future targets for therapy (gene therapy or chemotherapy), as previously reported in various human cancers [37], [47], [53], [64], [72].…”
Section: Discussionmentioning
confidence: 54%
“…An over-expression of this gene has been previously observed in human cervical cancer, invasive breast carcinoma, human astrocytoma, human pituitary adenoma, and canine osteosarcoma [31], [34], [35], [36], [10]; in addition, the relative expression of serum circulating CCNB2 mRNA in human cancer patients was significantly higher than in normal controls and benign disease group, and significantly correlated with cancer stage and metastasis status. Thus, it may have potential clinical applications in screening and monitoring of metastasis and therapeutic treatments [37].…”
Section: Discussionmentioning
confidence: 99%
“…For example, BUB1 mRNA was significantly co-expressed with AURKB mRNA in advanced-stage ovarian serous carcinoma [34]. Another study found that the circulating CCNB2 mRNA level in serum was significantly correlated with cancer stage and metastasis status [35]. …”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction and real-time RT-PCR were performed as previously described [31]. The primer sequences were previously described [22].…”
Section: Methodsmentioning
confidence: 99%